Medicare : preparing for the challenges of the 21st century - Reischauer, Robert D. (Robert Danton), 1941-; National Academy of Social Insurance (U.S.) Conference 1996 : Washington, D.C.) (Washington, D.C. : Distributed worldwide by Brookings Institution Press, 1998)
Papers presented at the ninth annual conference of the National Academy of Social Insurance, which was held in Washington, D.C., on Jan. 23-24, 1996.
Contract and Medicare reform / Stuart Butler -- Pundits, people, and Medicare reform / Theda Skocpol -- Reflections on how Medicare came about / Robert M. Ball -- Social insurance commentary / E.J. Dionne -- Preparing for the retirement of the baby boomers / Joseph R. Antos -- Medicare beneficiary as consumer / Stan Jones -- Structuring choice under Medicare / Roger Feldman and Bryan Dowd -- Restructuring Medicare : the role of public and private purchasing alliances / James C. Robinson and Patricia E. Powers -- Carve-outs for Medicare : possible benefits and risks / Melinda Beeuweks Buntin and David Blumenthal -- Medicare Fee-for-Service system : applying managed care techniques / Peter D. Fox -- Organizational models for restructuring Fee-for-Service Medicare / David G. Smith -- Leadership and politics : four views / Anthony Beilenson, Sheila Burke, Haynes Johnson, and John Rother -- Public opinion and Medicare restructuring : three views / Karlyn Bowman, Robert J. Blendon, and Celinda J. Lake.
Papers presented at the ninth annual conference of the National Academy of Social Insurance, which was held in Washington, D.C., on Jan. 23-24, 1996.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Medicare; Medicare -- Congresses; Medicare -- Forecasting -- Congresses; Medicare; Medicare -- Forecasting -- Congresses; Medicare; Medicare -- Congrès.; Medicare -- Prévision -- Congrès.; Medicare -- Prévision -- Congrès.; Medicare; MEDICAL -- Medicaid & Medicare; Medicare; Medicare -- Forecasting; Kongress; MEDICAL / Health Policy; Medicare -- Congresses; Medicare -- Forecasting -- Congresses; Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings; Actes de congrès.